Development and evaluation of an algorithm to facilitate drug prescription for inpatients with feeding tubes - Lohmann, Kristina; Freigofas, Julia; Leichsenring, Julian; Wallenwein, Chantal; Haefeli, Walter E.; Seidling, Hanna (European journal of clinical pharmacology, 2015)
We aimed to develop and evaluate an algorithm to facilitate drug switching between primary and tertiary care for patients with feeding tubes.
Gesehen am 02.06.2020